COOKIE LAND LEVEL 1 - Mitchell ,H.Q (MM PUBLICATIONS (E. MOUTSOU & CO O.E.), 2005)
Join Ricky, Lulu and Sam as they journey to Cookie Land to save the cookie population from the terrifying Big Mouth! This enchanting tale is sure to delight young readers and make them very hungry, too.